Meat Quality and Muscle Tissue Proteome of Crossbred Bulls Finished under Feedlot Using Wet Distiller Grains By-Product - Baldassini, Welder [UNESP]; Gagaoua, Mohammed; Santiago, Bismarck [UNESP]; Rocha, Leone [UNESP]; Torrecilhas, Juliana [UNESP]; Torres, Rodrigo [UNESP]; Curi, Rogério [UNESP]; Neto, Otávio Machado [UNESP]; Padilha, Pedro [UNESP]; Santos, Felipe [UNESP]; Lanna, Dante Pazzanese; Chardulo, Luis Artur [UNESP] (MDPI, 2022)
Wet distiller grains (WDG) are a corn by-product rich in protein and fiber that can be used in feedlot diets. This study evaluated F1 Angus-Nellore bulls fed on a control diet vs. WDG (n = 25/treatment). After a period of 129 days on these feeds, the animals were slaughtered and Longissimus thoracis samples were collected for both a meat quality evaluation and gel-based proteomic analyses. A greater ribeye area (99.47 cm²) and higher carcass weight (333.6 kg) (p < 0.05) were observed in the WDG-finished cattle compared to the control (80.7 cm²; 306.3 kg). Furthermore, there were differences (p < 0.05) in the intramuscular fat between the WDG and control animals (IMF = 2.77 vs. 4.19%), which led to a significant decrease (p < 0.05) in saturated fatty acids (FA). However, no differences (p > 0.10) were observed in terms of tenderness, evaluated using Warner–Bratzler shear force (WBSF). The proteomic and bioinformatic analyses revealed substantial changes in the biological processes, molecular functions, and cellular components of the WDG-finished cattle compared to the control. Proteins related to a myriad of interconnected pathways, such as contractile and structural pathways, energy metabolism, oxidative stress and cell redox homeostasis, and transport and signaling. In this experiment, the use of WDG supplementation influenced the protein expression of several proteins, some of which are known biomarkers of beef quality (tenderness and color), as well as the protein–protein interactions that can act as the origins of increases in muscle growth and reductions in IMF deposition. However, despite the effects on the proteome, the tenderness, evaluated by WBSF, and fatty acid profile were not compromised by WDG supplementation.
Keywords: beef quality; cattle; feedlot; mass spectrometry; nutrigenomics; proteome; skeletal muscle